Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Agresivitas Pajak dengan Profitabilitas sebagai Variabel Moderasi - Nurfalah, Sunita; Jaya R, Tresno Eka; Prihatni, Rida (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of liquidity and company size on tax aggressiveness with profitability as a moderating variable. The research method used is quantitative with secondary data. The population in this research is energy and basic materials sector companies listed on the IDX in 2020-2022. The sampling technique uses a purposive sampling method. The final number of observations in this study was 88 data. The data analysis method uses panel data regression analysis which is processed using Eviews 12 software. The results of this research show that the profitability variable has a positive effect on tax aggressiveness. Company size has no effect on tax aggressiveness. Profitability has no effect on tax aggressiveness. Profitability cannot moderate the influence of liquidity on tax aggressiveness. Profitability cannot moderate the effect of the relationship between company size and tax aggressiveness.